2007
DOI: 10.1177/039139880703000109
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Extended Nerve Defects with an Artifcial Nerve Graft Containing Schwann Cells Pre-Seeded on Polyglactin Filaments

Abstract: A 24 mm long bioartificial nerve graft (BNG) was created to bridge extended peripheral nerve defects of the rat sciatic nerve. In our previous studies, an identical graft had demonstrated good results over nerve gaps of up to 15 mm. The BNG device comprised a collagen-I tube filled with ten Schwann-cell-seeded polyglactin filaments and 106 isogenic Schwann cells suspended in Matrigel which were implanted in 27 rats (group I). Schwann-cell-free grafts (27 rats) and nerve autografts (18 rats) served as controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…Isogeneic SC-seeded guides gave a lower recovery result, while syngeneic SCs did not appear to enhance the regeneration process. Lohmeyer et al (2007) fi lled a collagen conduit with polyglactin (a synthetic absorbable polyester commonly used as suturing material) fi laments seeded with SCs and isogenic SCs suspended in Matrigel and used it to repair a 20-mm sciatic nerve gap in a rat model. Although the number of myelinated axons, which crossed the gap to reach the distal stump, was signifi cantly greater in the SC-seeded conduits than those in unseeded ones, the number of regenerated axons was still insuffi cient to regain the motor function.…”
Section: Nociceptive Functionmentioning
confidence: 99%
“…Isogeneic SC-seeded guides gave a lower recovery result, while syngeneic SCs did not appear to enhance the regeneration process. Lohmeyer et al (2007) fi lled a collagen conduit with polyglactin (a synthetic absorbable polyester commonly used as suturing material) fi laments seeded with SCs and isogenic SCs suspended in Matrigel and used it to repair a 20-mm sciatic nerve gap in a rat model. Although the number of myelinated axons, which crossed the gap to reach the distal stump, was signifi cantly greater in the SC-seeded conduits than those in unseeded ones, the number of regenerated axons was still insuffi cient to regain the motor function.…”
Section: Nociceptive Functionmentioning
confidence: 99%
“…Isogeneic Schwann cell-seeded guides gave a lower recovery result, while syngeneic Schwann cells did not appear to enhance the regeneration process [209]. Lohmeyer et al [210] filled a collagen conduit with polyglactin (a synthetic absorbable polyester commonly used as suturing material) filaments seeded with Schwann cells and isogenic Schwann cells suspended in Matrigel and used it to repair a 20-mm sciatic nerve gap in a rat model. Although the number of myelinated axons, which crossed the gap to reach the distal stump, was significantly greater in the Schwann-cell seeded conduits than those in unseeded ones, the number of regenerated axons was still insufficient to regain the motor function.…”
Section: Schwann Cellsmentioning
confidence: 99%
“…Although the number of myelinated axons, which crossed the gap to reach the distal stump, was significantly greater in the Schwann-cell seeded conduits than those in unseeded ones, the number of regenerated axons was still insufficient to regain the motor function. This might be due to granuloma formation or the foreign body reaction caused by degraded polyglactin filaments, which either physically hindered the regeneration process or adversely affected cell function [210]. Ishikawa et al examined the effect of chitosan gel sponges containing BMSC derived Schwann cells on peripheral nerve regeneration using a rodent model and concluded that the Schwann-cell seeded chitosan sponge could be a good potential candidate for neural repair [211].…”
Section: Schwann Cellsmentioning
confidence: 99%
“…The Schwann cell conduits resulted in larger axonal densities and diameters than the controls without Schwann cells. [129] To attempt to achieve results comparable to those produced by autografts, small intestinal submucosa (SIS) conduits filled with Schwann cells were implanted. These conduits were more effective than conduits without Schwann cells.…”
Section: Schwann Cell Transplantationmentioning
confidence: 99%